The Impact of Stronger Intellectual Property Rights on Science and Technology in Developing Countries (2005)
Introduction. 1. Old debates over IPR in developing countries. 2. The new, global debates. 3. Changes in the IPR regime and their impacts. 4. TRIPs and WTO. 5. Trade-relating IPR and the international division of labor. 6. Trade-relating IPR and the international division of labor. 7. International scientific collaboration and the Bayh-Dole Act. 8. Patenting of Research Tools and Database Protection. 9. Biodiversity. 10. Ethnic knowledge. 11. IPRs, north-south models and development policies: concluding remarks. References.